ANALISIS PENGUKURAN KEEFEKTIFITASAN SISTEM PRESENSI PEGAWAI MENGGUNAKAN METODE PIECES FRAMEWORK PADA BDK PALEMBANG - Prasiska Adela Susilowati; Tata Sutabri (Jurnal Komunikasi, 2023)
The presence of employees at the Palembang Religious Education and Training Center now uses epresence, namely the heritage application. The attendance data on e-presence or heritage is processed by the Civil Service Bureau of the Indonesian Ministry of Religion, making it possible that the application has weaknesses and strengths. Therefore, the application of the presence application needs to be evaluated and identified problems, in order to obtain user perceptions in order to develop the next version that is better and suits the user experience, as well as the level of satisfaction with using the application. The PIECES framework (Performance, Information, Economic, Control, Efficiency, Service) is a method that helps to evaluate and measure the level of user satisfaction. And the results of the measurements that have been carried out show the effectiveness of the presence system, namely at a Neutral number